Conference reports of the 7th (22-23 September 1993, Tromsö, Norway) and 8th (8-10 September 1994, Kaamanen, Finland) Nordic Workshops on Reindeer Research - Haugerud (Editor), Rolf Egil (Rangifer, 1995)
The workshops (conferences) were held in Tromsø (1993) and Kaamanen (1994) each with about 70 participants. The main themes in Tromsø were "Reindeer - pastures and environment in the Barents Euro Arctic Region (BEAR)" and in Kaamanen "European Union (EU) and the Reindeer Husbandry in Fennoscandia".